Navigating fear: Exploring speaking problems among students at junior high school level - Palomargareta, Gebriela; Astutik, Yuli (Journal of Research on English and Language Learning (J-REaLL), 2024)
This study delves into the intricacies of speaking problems encountered by junior high school students while learning English. Employing a descriptive qualitative approach, six participants representing both high and low proficiency levels were selected from a private junior high school in Sidoarjo, Indonesia. Data collection involved observation and interviews based on Ur’s (1991) framework of speaking problems, encompassing inhibition, lack of content, uneven participation, and native language interference. The research findings revealed that students across proficiency levels faced speaking problems. Interestingly, junior high-level students also have difficulty speaking in English class. While observation data suggested a discrepancy in speaking problems between high and low students, in-depth interviews uncovered shared challenges. Notably, inhibition, lack of content, and native language interference were prevalent among participants. These findings underscore the imperative for students to bolster confidence in speaking English through consistent practice inside and outside the classroom. Furthermore, educators must enhance their pedagogical strategies, particularly in cultivating diverse speaking skills to facilitate students’ English language acquisition.